Effect of drying methods and extraction solvents on phenolic antioxidants and antioxidant activity of Scurrula ferruginea (Jack) danser (Loranthaceae) leaf extracts - Vanielie Terrence Justine; Muskhazli Mustafa; Kankara, Sulaiman S.; Rusea Go (Penerbit Universiti Kebangsaan Malaysia, 2019)
Scurrula ferruginea is a type of mistletoe from the Loranthaceae family found in Southeast Asia and distributed in tropical regions, is known to have healing effects for many disorders. Preservation of the bioactive metabolites is dependent on the sample preparation and drying methods as well as extraction solvents used. Thus, the present study was carried out to investigate the effect of different drying methods and extraction solvents on the total phenolic and the antioxidant activities of S. ferruginea leaves. The leaves of S. ferruginea were air and oven (60°C) dried and extracted with aqueous, organic and aqueous-organic solvents. The total phenolic content (TPC) and total flavonoid content (TFC) were used to gauge the phenolic antioxidants extracted, while the antioxidant activity was evaluated by measuring the scavenging effect on 2,2- diphenyl-1-picrylhydrazyl (DPPH) radical and via the ferric reducing antioxidant power (FRAP) assay. The optimum conditions obtained were oven drying, 80% acetone with values of 3.47 mg/10 g DW (extract yield), 171.29 mg GAE/1 g DW (TPC), 31.91 mg QE/1 g DW (TFC), 93.2% (DPPH), 26.41 mg TE/1 g DW (FRAP) and 7.41 μg/mL (IC50). The present findings suggested that sample preparation variability using different drying methods and solvents for extraction play a crucial role in enhancing the efficiency of extraction and efficacy of the antioxidant compounds in S. ferruginea leaf extracts.